(untitled) (Journal of the College of Basic Education, 2026)
This Study elaborates on the synthesis and nonlinear optical characteristics of gold (Au) and zinc oxide (ZnO) nanoparticles and nanocomposites (ZnO-Au NCs), which are prepared by pulsed laser ablation in liquid (PLAL) approach. ZnO is a year-wide bandgap semiconductor with high exciton binding energy (60 meV) that is economical, environmentally friendly, and non-toxic thus it is suitable in optical and electronic devices. Characterizations of the synthesized nanoparticles were done by X-ray diffraction (XRD), energy dispersive X-ray (EDX), ultraviolet-visible (UV-Vis) spectroscopy, Fourier-transform infrared (FTIR) spectroscopy, field emission scanning electron microscopy (FESEM), and transmission electron microscopy (TEM). The results show that, ZnO- Au nanocomposites have better nonlinear optical properties than the original Au and ZnO nanoparticles. The nonlinear refractive index (n2) of ZnO-Au NCs was determined to be 3.27 x 104 cm2 /GW, which is much higher than that of pure ZnO (3.7 x 104 cm2 /GW ). Another technique used in the study to obtain the nonlinear optical parameters was the Z-scan in which, it was found that the inclusion of Au in ZnO increases light absorption by the surface plasmon resonance (SPR) effect. The study exudes the potential of ZnO-Au nanocomposites in the future of the design of advanced nonlinear photonic devices and environmental remediation, which is a clean and efficient way of synthesizing functional nanomaterials.